(untitled) - Smith, Lawrence D. (Hoboken, N.J., 2005)
Architects, interior designers, preservationists, and anyone who is interested in the details of Federal Style architecture will find this a valuable resource
Keywords: Interior architecture,Interior architecture,Decoration and ornament,Kiến trúc nội thất,Kiến trúc nội thất; History,History,Federal style,Lịch sử,Lịch sử; 18th century,19th century,Thế kỷ 18,Thế kỷ 19; New England,New England,New England,New England,New England